Changing Identities: Chinese Muslims' Marriage Strategies in Late Ming Quanzhou. (3rd July 2017) - Li, Guotong
Abstract : Recent scholarship on early Ming sinification policies has revealed that the founding emperor of the Ming, Zhu Yuanzhang, carried out a series of reforms to revive Chinese features in his people which targeted the influence of Mongols and other foreigners on the empire, including enforcement of intermarriage between Chinese and non-Chinese to prohibit endogamy within non-Chinese groups. Endogamy had long been used as an effective means to consolidate the purity and ensure the continuity of Muslim communities in China. This study examines how the imperial state's policy of mandatory intermarriage affected Muslim marriage choices by analyzing marital values, marriage strategies, and the adjustments of family practice in intermarried households. In this way, gender, through marriage strategies, played a critical role in Chinese Muslims' changing identities.